Verticalidade foliar e interceptação de luz: eficiência de conversão em biomassa - Beraldo, Amanda Naves [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The light capture is a low efficiency process in plants, as they effectively use only 8% sunlight. A better distribution and penetration of sunlight within the plant canopy is observed in plants with vertical leaves (paraheliotropic and/or static vertical leaves) because light may be intercepted by both leaf surfaces (adaxial and abaxial sides). By doing so, photoinhibition, water deficit, leaf heating, irradiance excess, and auto-shading are minimized. These responses have been studied using momentary measured parameters (leaf gas exchange and chlorophyll fluorescence), however little is known about the effects of different leaf angles on the conversion of sunlight into biomass. We have tested the hypothesis that the biomass production in plants with leaves artificially maintained at the vertical position is higher than those with leaves forced at the horizontal position. We used pots (50 L) to cultivate 30 sugar-cane plants (Saccharum oficinarum L. cv. IACSP95-5000), of which ten had their leaves kept at the vertical position, ten had their leaves kept at the horizontal position and ten grew naturally (control). During cultivation, the leaves were counted every two weeks. After seven months, leaves area (AF, cm2) were determined and the distinct plant organs (Leaves, stems, sheaths and roots) were set apart and oven-dried (60C) until obtaining constant dry mass (g). Data was submitted to a one-way analysis of variance (ANOVA), and mean results accompanied by the Tukey test (α = 5%). There was no significant difference in height between control plants and those with leaves arranged vertically; however, the height of the plants with leaves arranged horizontally was lower than both treatments. The aerial biomass was higher in plants with leaves arranged vertically in relation to other treatments, resulting in 22.9% and 15% more mass in relation to plants with leaves set...

A captação e processamento da luz pelas plantas é pouco eficiente, visto que apenas 8% da luz é aproveitada. Um melhor aproveitamento da luz é observado em plantas com folhas verticais (paraheliotrópicas e/ou verticais estáticas) porque a luz incide nas faces adaxial e abaxial. Desta forma, a fotoinibição, o déficit hídrico, o aquecimento foliar, o excesso de irradiância e o auto sombreamento são minimizados. Todas essas respostas têm sido estudadas usando variáveis momentâneas (trocas gasosas e fluorescência da clorofila), porém pouco se conhece sobre os efeitos das diferentes disposições foliares na conversão de energia luminosa em biomassa. Testamos a hipótese de que a biomassa de plantas com folhas artificialmente dispostas na vertical é maior que naquelas em que as folhas são forçadas na horizontal. Cultivamos em vasos (50 L) 30 plantas de cana-de-açúcar (Saccharum oficinarum L. cv 'IACSP95-5000'), em que 10 plantas tiveram suas folhas mantidas na vertical, 10 mantidas na horizontal e 10 cresceram naturalmente (controle). Durante o cultivo, as folhas foram contadas a cada quinze dias. Após sete meses de cultivo, todas as plantas tiveram sua área foliar (AF, cm2) determinada, e seus diferentes órgãos (folhas, colmos, bainhas e raízes), foram separados e secos (60°C) até obtenção de massa seca constante (g). Os dados foram submetidos à análise de variância (one-way ANOVA) e as médias, comparadas pelo teste de Tukey (α= 5%). Não houve diferença significativa na altura entre as plantas controle e as com folhas dispostas verticalmente; entretanto, a altura das plantas com folhas dispostas na horizontal foi inferior a ambos os tratamentos. A biomassa da parte aérea foi superior nas plantas com folhas dispostas verticalmente em relação aos outros tratamentos, resultando em 22,9% e 15% a mais de massa em relação às plantas com folhas...
Keywords: Fisiologia vegetal; Analise foliar; Plantas - Efeito da luz; Plantas - Fotomorfogênese; Plantas - Analise; Biomassa vegetal; Folhas - Anatomia; Fotossintese